SCUDERI SPLIT CYCLE ENGINE: REVOLUTIONARY TECHNOLOGY & EVOLUTIONARY DESIGN REVIEW - Prof. Dattu Balu Ghane (International Journal of Innovations in Engineering Research and Technology, 2021)
The IC engine has seen numerous revolutionary and evolutionary modifications in technology and design over the past few decades. The sole motto behind the modifications was to increase the overall efficiency of the IC Engine including volumetric and thermal efficiency. Recently few benchmarking technologies like the CRDI, MPFI, HCCI, etc. in the Otto cycle and Diesel cycle engines have created an enormous revolution in the automobile industry. In spite of these technological and design advances, the efficiencies are not being more than a particular limit.However, the concept of split cycle engines has drastically increased the overall performance in all respect.The split cycle concept basically separates the four strokes of the conventional cycle. The Scuderi engine one of the best-in-class engine designs based on the split cycle concept.